Gestión de procesos de diseño aplicado a la estilización de indumentaria basado en fibra de alpaca - Irlanda Beatriz, Aroca Castillo (2021)
ABSTRACT: Ecuadorian craftsmanship immersed in textiles and clothing focused on the development of traditional products, that have shown a decline due to the industrialization of production processes, to obtain products where the craft skills and their essence have been fading Due to the influence of mass production, environmental exploitation and the limited knowledge about the benefits of its raw materials, one of them is alpaca fiber, which could be exploited thanks to its versatility and value appreciated since the time of the Incas who worked this fiber only for royalty, and it ruined due to Spanish intervention. On the other hand, this raw material is not well known in the elaboration of clothing products under factors such as added value, dynamics of alpaca production, and the improvement of the ecosystem, the rural areas are not managed with the due legal, political and social argument. The objective of the research is to elaborate design processes applied to the stylization of clothing based on alpaca fiber, through the strengthening of assembly sequences to revalue the handicraft work in the community of Palacio Real, because there are antecedents that review this problem from the point of view of fiber production and large-scale marketing of existing products. To clarify the dynamic of this research is sought to combine a qualitative methodology that directs explorative, explanatory, and quasi-experimental research to correlate artisan work with manufacturing processes and obtain the benefits for artisans who maintain the culture and tradition of its people.